PENGARUH KONTEN INFOGRAFIK INSTAGRAM @PANDEMICTALKS TERHADAP SIKAP WASPADA FOLLOWERS DI MASA PANDEMI.(Studi Pada Followers Akun @Pandemictalks di Jakarta) - Muthiya Natasha, (2021)
In 2020, the Covid19 outbreak appeared, which is a new virus that attacks the human respiratory system. Pandemictalks utilize social media, namely, Instagram to spread credible literacy about Covid19 in the form of infographics that are easily understood by the audience, especially its followers. This study aims to determine the influence the Instagram @Pandemictalks infographic content has on the alert attitude of followers during a pandemic. The theory used is Information Integration. This research uses quantitative research methods with explanative research type. This study uses a questionnaire for data collection. The results showed that the influence of Instagram @pandemictalks infographic content was 73.7% on the alert attitude of followers. The results of the correlation indicate that there is a very strong relationship between the infographic content on Instagram @pandemictalks and the alert attitude of followers. So it can be concluded that the valence factor and the weight of the assessment mentioned in the integration information theory, and linked to the @pandemictalks infographic content are aligned so as to encourage the alert attitude of followers. The suggestion in this research is that the @pandemictalks Instagram account is expected to continue infographic content about Covid19 to continue to serve as a reminder for the community, especially @pandemictalks followers to maintain a vigilant attitude towards Covid19.